A liquefied gas thruster for a micro satellite - Joubert, Adriaan Jacobus (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.